Flow analysis around Kuching Barrage by field measurement and Large Eddy Simulation turbulence model using 3D Computational Fluid Dynamics - Khairil Anuar, Nurul Izzah; Ibrahim, Saerahany Legori; Nik Hassan, Nik Mohd Kamel; Ibrahim, Izihan; Ramli, Muhammad Zahir (UTS Publisher, 2025)
This study investigates the hydrodynamic complexity of turbulent flow conditions near the Kuching Barrage in the Sarawak River using field measurements and 3D Computational Fluid Dynamics (CFD) simulations FLOW-3D. Upstream and downstream of the barrage, Acoustic Doppler Current Profilers (ADCPs) were used to collect field data, which was then incorporated into a Large Eddy Simulation (LES) model to simulate the hydrodynamic properties. Riverbed surveys and sediment sampling enabled the model's implementation. The results showed good agreement between the modeled and measured data, providing evidence of the simulation's accuracy. It was demonstrated in the study that 3D modeling is essential for resolving complex dynamics associated with flow, which cannot be adequately addressed by conventional 1D or 2D methods. To improve the validity of future studies, future measurements should be prioritized, and finer computational grids should be more implemented.